Virtual simulation-based study on sports anatomy: technological applications and future development - Xiao, H.; Re, J.; Ling, H.; Jiang, C.; Wang, P. (American Journal of Sports Science, 2023)
This paper explores the technological applications and future development of virtual simulation technology in sports anatomy research. It begins by providing a comprehensive overview of how virtual simulation has been utilized in studying bones, muscles, and joints. This includes skeletal modeling and biomechanical analysis, muscle mechanics research, kinematic analysis of joints, and posture and movement optimization. The paper then delves into the various technological applications of virtual simulation in sports anatomy research. It discusses modeling and simulation techniques, motion capture and pose estimation, force feedback and physical simulation, as well as soft tissue modeling and simulation. Furthermore, the paper presents an outlook on the future development directions and research prospects of virtual simulation in sports anatomy. It highlights the integration of virtual reality and augmented reality as well as the application of artificial intelligence technology. The paper also mentions the importance of interdisciplinary integration and collaboration. In conclusion, this paper summarizes the innovations and contributions it has made in exploring virtual simulation technology in sports anatomy research. It emphasizes the significance of virtual simulation in this field and its potential for further development. Researchers in sports anatomy will find this paper valuable as it provides references for their work and contributes to the overall development and innovation of the domain.